Análise da qualidade superficial no fresamento do aço AISI P20 com utilização de ferramentas com tratamento e sem tratamento do gume - Rodrigues, Fabiano Ramos (My University, 2025)
This work addresses the application of drag polishing on carbide end mills, emphasizing the importance of machining processes in the global production and economic chain. With the constant evolution of technology in machining equipment, it is crucial to ensure that tools can withstand the loads applied during machining processes. The need for high production rates and competitiveness drives the search for more efficient and reliable tools, processes, and equipment, providing study opportunities in various areas such as tools, materials, machines, processes, removal strategies, and cutting fluids. In the context of tools, this work focuses on the effects of tool preparation through abrasive media drag polishing. The chosen material for the tests is SAE P20 steel, widely used in molds and dies, especially for polymeric materials. Considering changes in the surface area, known as surface quality, caused by contact with polymeric materials, the study includes experimental tests comparing original tools and tools polished by the drag polishing method with abrasive media. One methodology involves performing a design of experiments (DOE) to assess whether the values generated by the system can be computed by the machining equipment. After this validation, machining is performed on different parts of the specimen, using the data generated by the DOE. The analysis of the specimen includes an evaluation of the roughness to examine the surface characteristics and the surface quality resulting from the machining. This study contributes to the advancement in the understanding of the effects of tensile polishing on carbide milling cutters, providing valuable data on the surface quality of specific materials, such as SAE P20 steel. The results obtained demonstrate that the cutting edge treatment resulted in improvements of approximately 12%, but it was not the predominant factor for the surface quality of the machined material. [resumo fornecido pelo autor]
Este trabalho aborda a aplicação de polimento por arraste em fresas de metal duro, destacando a importância dos processos de usinagem na cadeia produtiva e econômica global. No contexto das ferramentas, este trabalho se concentra nos efeitos da preparação da ferramenta por meio do polimento por mídia abrasiva. O material escolhido para os testes o aço SAE P20, amplamente utilizado em moldes e matrizes, especialmente para materiais poliméricos. Considerando as mudanças na área superficial, denominada qualidade superficial, o estudo inclui ensaios experimentais comparando ferramentas originais e ferramentas polidas pelo método de arraste em mídia abrasiva. A metodologia envolve a execução de um planejamento de experimentos (DOE) para avaliar se os valores gerados pelo sistema podem ser computados pelo equipamento de usinagem. Após essa validação são realizadas usinagens em diferentes partes do corpo de prova, utilizando os dados gerados pelo DOE. A análise do corpo de prova inclui a avaliação da rugosidade para a qualidade superficial resultante da usinagem. Este estudo contribui para o avanço no entendimento dos efeitos do polimento por arraste em fresas de metal duro, proporcionando dados valiosos sobre a qualidade superficial em materiais específicos, como o aço SAE P20. Os resultados obtidos demonstram que o tratamento do gume resultou em melhorias aproximadas de 12% , porém não foi o fator predominante para qualidade superficial do material usinado. [resumo fornecido pelo autor]
Keywords: Usinagem; Fresagem (Trabalhos em metal); Retificação e polimento; Máquinas-ferramenta; Ferramentas; Aço; Engenharia mecânica; Machining; Milling (Metal-work); Grinding and polishing; Machine-tools; Tools; Steel; Mechanical engineering